Fifth Five Year Plan 1974-79 A Draft Outline Government of Kerala - Planning Commission (Planning Commission, 1974)
Even as economic planning initiated the process of development it hardly produced the desired impact on the economy of the State. The first two Plans were grossly inadequate in respect of both the scale and content of developmental efforts. Despite substantially increased outlay on the Third Plan and the subsequent annual plans the crucial sectors of the economy-agriculture and industry-registered sluggish growth. The Fourth Plan accordingly envisaged a growth rate large enough to bridge the gap between per capita regional income and the per capita national income in a period of 15 years. As it turned out this consummation devoutly wished for was not in sight if the performance in the first three years of the Plan is any index.
State Planning Board Trivandrum Government of Kerala